PREVALENCE OF PULMONARY HYPERTENSION IN PATIENTS OF CHRONIC KIDNEY DISEASE IN WESTERN RAJASTHAN: A CROSS-SECTIONAL STUDY - VYAS, SWATI; YADAV, POOJA; RP, AGRAWAL (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: We organized a study to determine the prevalence of pulmonary hypertension (PHT) in individuals with chronic renal disease, because there has not been much research on this topic in our area. Studying any relationships, if any, between PHT and chronic kidney disease (CKD) stage was another goal. Methods: A hospital-based cross-sectional study of 108 CKD cases was carried out (according to various phases based on glomerular filtration rate) and included participants over the age of 18. SPSS software was used to collect and analyze all data. Correlation was determined using the corelation coefficient. Results: About 15.74% of people with CKD had PHT. Patients’ PHT was mild in 47.06% of cases, moderate in 41.18% of cases, and severe in 11.11% of cases. The correlation between the stage of CKD and PHT was determined to be statistically negligible. Age, CKD stage and duration, and PAH were revealed to be statistically unimportant in linear regression. Conclusion: About 15.74% of CKD patients had PHT, according to the study. The age of the patients, the length of the CKD, and the stage of the CKD were positively correlated with PHT.